2001
DOI: 10.1590/s0102-311x2001000600018
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de HIV, papilomavírus humano e sífilis na Penitenciária Feminina da Capital, São Paulo, 1997-1998

Abstract: Incarcerated women as a group are particularly vulnerable to infections. The lack of public programs for prevention, early diagnosis, and treatment contribute to the increase in the incidence and prevalence of diseases in general and especially sexually transmitted diseases. This article aims to estimate the prevalence of infection by the human immunodeficiency virus (HIV), human papillomavirus (HPV), and syphilis among inmates at the Women's Penitentiary in the State capital of São Paulo, Brazil. All inmates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1
40

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 20 publications
3
15
1
40
Order By: Relevance
“…Outros estudos apresentam resultados bem próximos, como é o caso do estudo de Lopes et al 14 , desenvolvido em São Paulo em 1998.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Outros estudos apresentam resultados bem próximos, como é o caso do estudo de Lopes et al 14 , desenvolvido em São Paulo em 1998.…”
Section: Discussionunclassified
“…Outros estudos internacionais observaram altas prevalên-cias como de 57,5% na prisão Australiana 23 Todos os estudos apresentados observaram associação da infecção do HCV com o uso de drogas. Embora, como destacamos acima, o risco da infecção pelo vírus da hepatite C esteja associado ao uso de drogas 4,8,14,21,22,23,24,25 , principalmente em seu uso parenteral, isto é, uso de droga injetá-vel, outra forma de transmissão que aparece cada vez mais consistente é a que se liga a aspectos do comportamento sexual, como a parceria com UDI.…”
Section: Discussionunclassified
“…Studies carried out in several countries, including Brazil, showed a high prevalence of HIV and syphilis infections in incarcerated men 3,5,10,11,12,13 and women 2,3,6,14,15,16,17,18,19,20,21 , reinforcing the importance of serological diagnosis in prisons for the implementation of available intervention. However, Brazilian studies have been carried out in isolated prison units.…”
Section: Introductionmentioning
confidence: 97%
“…3,15 In Brazil, there are few studies that deal with the health of this population and, in general, they refer to specifi c groups such as the adolescents, 9 minor offenders, 24 or female prisoners. 8 Lopes et al 8 found prevalences of 14.5% for HIV infection and 5.7% for syphilis in a female prison in the city of São Paulo. They concluded that poverty and low level of education were important risk factors for sexually transmitted diseases, including HIV/AIDS.…”
Section: Introductionmentioning
confidence: 98%